IMPLEMENTATION OF THE INDONESIAN ELECTRONIC HAJJ HEALTH CARD (KKJH) SERVICE IN MEDAN CITY - Novita Anis Zai; Siti Hazzah Nur R (Yayasan Wayan Marwan Pulungan, 2023)
The Electronic Hajj Health Card Service for Indonesian Pilgrims (KKJH) is one of the Public Service programs with a background in changing the service system from manual to electronic. The Indonesian Electronic Hajj Health Card Service Program (KKJH) is implemented with the aim of Ease of Service by health workers because the medical history of prospective pilgrims (CJH) is more complete, organized, dynamic, and up to date. Apart from that, this program also adapts to the paperless era but in practice the implementation of the program is not evenly distributed between officers so that the information received by the community is not evenly distributed. This study aims to describe in detail how public services through the Implementation of Indonesian Electronic Hajj Health Card Services (KKJH) in Medan City use descriptive research methods with a qualitative approach.The data obtained were analyzed qualitatively with the implementation theory approach by Charles Jones which includes organization, interpretation, and application.The results of the study show that the Medan City Health Office must further enhance cooperation with the Main Health Center such as the Padang Bulan Health Center UPT so that the socialization process can be better understood by health workers so that health workers at the health center can carry out the program effectively and the public will understand more about the main function of Health Hajj Card Services Hajj (KKJH) Electronic Indonesia).